Double-Positive Anti-GBM and ANCA Vasculitis: 2 Case Reports and Review of the Literature - Selim, Benhadda; Manal, Nmili; Nada, Nassiri; v, Benamar; Naima, Ouzeddoun; Tarik, Bouattar (Journal of Clinical Nephrology, 2025)
Double-Positive Patients (DPPs), characterized by the simultaneous presence of Anti-Neutrophil Cytoplasmic Antibody (ANCA) and anti-Glomerular Basement Membrane (anti-GBM) antibodies, represent a rare subset in systemic vasculitis. We present two cases of DPPs with renal involvement and review the existing literature to elucidate the clinical characteristics, histopathological findings, management strategies, and prognostic outcomes associated with this condition. Both cases exhibited renal involvement with rapidly progressive glomerulonephritis, requiring renal replacement therapy. Renal biopsies confirmed crescentic glomerulonephritis with features of both anti-GBM disease and ANCA-associated vasculitis. Management included high-dose glucocorticoids, cyclophosphamide, and consideration of plasma exchanges. Double-positive ANCA and anti-GBM vasculitis pose challenges in management and prognosis. Further research is essential to improve therapeutic strategies for this rare and heterogeneous condition.